Port green investment strategy under government subsidization and regulation policy - Xie, Fengjue; Zhou, Zhongyin (Frontiers in Marine Science, 2025)
The greener port has become an important goal for the maritime industry. This paper developed an economic model to discuss how the investment effectiveness and two commonly used governmental policies (regulation and subsidy policies) affect port’s output, green investment, and governmental policy choices. Findings show that compared to no policy, both policies promote green investment, but their impacts on output are opposite: regulation restrains output, while subsidies boost it. Subsidies, as a proactive tool, reduce ports’ green investment costs, driving both investment and output—especially in initial stages with high subsidy rates (0.3-0.5) covering over 50% of costs. Regulation, more passive, forces ports to increase investment but limit production, particularly when investment efficiency is low. Investment effectiveness shapes policy selection: subsidies work better at low or high efficiency, while regulation is preferable at medium efficiency. Both policies outperform no intervention in improving social welfare. These insights inform policy design for sustainable port development.